2011
DOI: 10.1073/pnas.1103247108
|View full text |Cite
|
Sign up to set email alerts
|

In vivo molecular imaging of peripheral amyloidosis using heparin-binding peptides

Abstract: Heparan sulfate proteoglycans (HSPGs) are ubiquitous components of pathologic amyloid deposits in the organs of patients with disorders such as Alzheimer's disease or systemic light chain (AL) or reactive (AA) amyloidosis. Molecular imaging methods for early detection are limited and generally unavailable outside the United Kingdom. Therefore, there is an urgent need to develop novel, specific amyloidophilic radiotracers for imaging to assist in diagnosis, prognostication, and monitoring response to therapy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
106
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(111 citation statements)
references
References 49 publications
4
106
1
Order By: Relevance
“…A number of marker metabolites for diagnosis and prognosis of HCC have been reported. 29,30 A UPLC-MS-based metabolomics approach has been used to characterize serum profiles from HCC, liver cirrhosis (LC), and healthy subjects, and the accuracy of UPLC-MS profiles and AFP levels were compared for their use in HCC diagnosis. 31 Thirteen potential biomarkers were identified that suggest there were significant disturbances of key metabolic pathways in HCC patients.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 99%
“…A number of marker metabolites for diagnosis and prognosis of HCC have been reported. 29,30 A UPLC-MS-based metabolomics approach has been used to characterize serum profiles from HCC, liver cirrhosis (LC), and healthy subjects, and the accuracy of UPLC-MS profiles and AFP levels were compared for their use in HCC diagnosis. 31 Thirteen potential biomarkers were identified that suggest there were significant disturbances of key metabolic pathways in HCC patients.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 99%
“…B10 shares these features with several biotechnologically generated amyloid-binding peptides, including p5 and D3 [24,25], as well as naturally occurring amyloidbinding proteins and pattern recognition receptors, such as serum amyloid P component, scavenger receptor, and receptor for advanced glycation end products. These amyloid-binding proteins all have positively charged ligand-binding sites, indicating that fibril recognition is primarily dependent on electrostatic interactions [32].…”
Section: Specificities and Molecular Recognition Mechanismsmentioning
confidence: 96%
“…Examples are the p5 peptide, which was obtained by phage-display selection against glycosaminoglycan (GAG) amyloid secondary components [24], as well as the D1 and D3 peptides, which were generated through Dmirror-image phage display [25]. This elegant method uses biotinylated D-Ab(1-42) peptide as a target such that conversion of the selected peptide into its D-amino acid counterpart enables binding to the natural L-amino acid Ab and also provides the general advantages of D-peptides.…”
mentioning
confidence: 99%
“…Probes for determining the in vivo amyloid load, and for monitoring treatment, include SAP, anti-AA antibodies, and HPSG ligands, in each instance controlling for possible cross-reactivity with circulating and soluble precursors in normal tissue and contiguous to fibrillar deposits (3,5,16,17). Studies carried out during SAA triggering by inflammatory stimuli and amyloid induction have shown an ∼90-min half-life and a large HDL APR SAA pool as a result of increased hepatic synthesis, only 0.01% of which is deposited in the mouse spleen over a 24-h period (18).…”
mentioning
confidence: 99%